2019
DOI: 10.1016/j.quascirev.2019.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Peat humification records from Restionaceae bogs in northern New Zealand as potential indicators of Holocene precipitation, seasonality, and ENSO

Abstract: In comparison with temperature reconstructions, New Zealand proxy records for paleo-precipitation are rare, despite the importance of precipitation in contemporary climate variability and for projected climate impacts. In this study, records of mid-late Holocene palaeomoisture variation were derived for two hydrologically separate ombrotrophic Restionaceae bogs in northern New Zealand, based on peat humification analysis. At each site, three cores were analysed for peat humification, facilitating both intra-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 101 publications
0
18
0
Order By: Relevance
“…Although this is a sound conceptual basis, questions have been raised about the general applicability of humification as a paleoclimatic or paleohydrological proxy because the humification-based peat-surface wetness reconstructions have been challenged by other proxies-based peat moisture records (Amesbury et al, 2012; Chambers et al, 2011; Hughes et al, 2012; Newnham et al, 2019; Yeloff and Mauquoy, 2006). The inconsistencies between humification and other proxies are most likely attributable to two reasons: (1) site-specific changes in peat botanical composition (Chambers et al, 1997; Hughes et al, 2012; Payne and Blackford, 2008; Zhang et al, 2017) and (2) locality-specific variations in topography and geochemistry of peat (Caseldine et al, 2000; Morgan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this is a sound conceptual basis, questions have been raised about the general applicability of humification as a paleoclimatic or paleohydrological proxy because the humification-based peat-surface wetness reconstructions have been challenged by other proxies-based peat moisture records (Amesbury et al, 2012; Chambers et al, 2011; Hughes et al, 2012; Newnham et al, 2019; Yeloff and Mauquoy, 2006). The inconsistencies between humification and other proxies are most likely attributable to two reasons: (1) site-specific changes in peat botanical composition (Chambers et al, 1997; Hughes et al, 2012; Payne and Blackford, 2008; Zhang et al, 2017) and (2) locality-specific variations in topography and geochemistry of peat (Caseldine et al, 2000; Morgan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistencies between humification and other proxies are most likely attributable to two reasons: (1) site-specific changes in peat botanical composition (Chambers et al, 1997; Hughes et al, 2012; Payne and Blackford, 2008; Zhang et al, 2017) and (2) locality-specific variations in topography and geochemistry of peat (Caseldine et al, 2000; Morgan et al, 2005). Newnham et al (2019) also challenged the use of humification and found that stronger longer-term trend of humification is attributed to slow anaerobic decay over time because the trend toward wetter summers in the late Holocene cannot be corroborated by independent climate proxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowe, 1988;Shane and Hoverd, 2002;Molloy et al, 2009;Shane et al, 2013;Hopkins et al, 2015Hopkins et al, , 2017Peti et al, 2020) (3) Bog settings (e.g. Lowe, 1988;Newnham et al, 1995Newnham et al, , 2007Newnham et al, , 2019Lowe et al, 1999Lowe et al, , 2013Gehrels et al, 2006), or (4) within terrestrially exposed (commonly marine or riverine) sediments, for example in the -Whanganui Basin (e.g. Seward, 1976, Naish et al, 1996Pillans et al, 2005;Rees et al, 2019), 140 -Wairarapa region (e.g.…”
Section: Geologic Settingmentioning
confidence: 99%
“…The central North Island of New Zealand has huge stores of buried, allophane-rich paleosols developed on sequences of well-dated tephra beds 16,17,23,24 . The early Holocene of this region was dominated by extensive podocarp-broadleaf forest and warm and wet conditions followed generally by gradual drying and cooling [25][26][27][28] with modest uctuations 29 . Thus, the slow carbon turnover rate in allophane-rich soils, and the abundance of buried allophanic paleosols on dated tephras in North Island, provide the opportunity to characterize the nature of stabilized SOM preserved in allophanic soils/paleosols in response to changes of environmental and climatic conditions.…”
Section: Introductionmentioning
confidence: 99%